El perfil geográfico de la delincuencia juvenil: Un análisis de las características espaciales asociadas a la movilidad delictiva de los jóvenes - Vázquez Morales, David (Revista Española de Investigación Criminológica, 2014)
The relationship between space and crime has been broadly analyzed by environmental criminologist. In Spain, given the lack of quantitative data, the knowledge on the topic is limited and makes it necessary to increase empirical research, especially in the field of juvenile delinquency. The present research uses a sample of 145 cases obtained from the regional court of Albacete in order to deepen the knowledge on the spatial characteristics of juvenile delinquency. The study carries out and exploratory data analysis (ESDA) in two stages. In the first stage, we analyze the spatial distribution of the juvenile crimes and residence of offenders by mapping the hotspots. Afterwards, in order to deepen on the determinants of the displacement of juvenile offenders from their homes to the spot where they commit their offences we carry out a confirmatory analysis by mean of regressions using the variables that the literature points out to be important.